2017
DOI: 10.1007/s10393-017-1268-3
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia miyamotoi, Other Vector-Borne Agents in Cat Blood and Ticks in Eastern Maryland

Abstract: We collected blood and tick samples in eastern Maryland to quantify vector-borne pathogen exposure and infection in healthy cats and to assess occupational disease risk to veterinary professionals and others who regularly interact with household pets. Thirty-six percent of healthy cats parasitized by ticks at time of examination (9/25) were exposed to, and 14% of bloods (7/49) tested PCR-positive for, at least one vector-borne pathogen including several bloods and ticks with Borrelia miyamotoi, a recently reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The primary tick species identified ( R. sanguineus , A. americanum , D. variabilis and I. scapularis ) constituted more than 95% of the ticks submitted from dogs, as was seen in earlier regional reports [6, 9]. Similarly, more than 80% of the ticks found on cats were A. americanum , I. scapularis , or D. variabilis , as has been described in previous surveys [2, 810]. Most pets with ticks had outdoor access, but a variety of tick species were submitted from a few dogs and cats that were reported to rarely or never go outside, suggesting ticks carried into the home on clothing or other pets may create a risk to indoor pets [2].…”
Section: Discussionsupporting
confidence: 75%
“…The primary tick species identified ( R. sanguineus , A. americanum , D. variabilis and I. scapularis ) constituted more than 95% of the ticks submitted from dogs, as was seen in earlier regional reports [6, 9]. Similarly, more than 80% of the ticks found on cats were A. americanum , I. scapularis , or D. variabilis , as has been described in previous surveys [2, 810]. Most pets with ticks had outdoor access, but a variety of tick species were submitted from a few dogs and cats that were reported to rarely or never go outside, suggesting ticks carried into the home on clothing or other pets may create a risk to indoor pets [2].…”
Section: Discussionsupporting
confidence: 75%
“…Dogs, cats and other domestic animals are susceptible to numerous potentially deadly tick‐borne bacterial and protozoal diseases, including Lyme disease, spotted fever rickettsioses, American canine hepatozoonosis, cytauxzoonosis and tick paralysis toxicosis (Bowman 2009 ; Chomel 2011 ; Kidd & Breitschwerdt 2003 ; Little et al., 2014 ; Nagamori & Reichard 2015 ; Reichard et al., 2010 ; Shaw et al., 2001 ). Even in cases where animals are asymptomatic or display sub‐clinical signs of tick‐borne disease infection, they can act as potential reservoirs for zoonotic pathogens (Fritz 2009 ; Mather et al., 1994 ; Shannon et al., 2017 ; Shaw et al., 2001 ). Several studies have demonstrated that those living in households with either dogs or cats are at higher risk of tick encounters and tick‐borne illnesses than those in households without pets (de Wet et al., 2020 ; Jones et al., 2002 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to B. burgdorferi s.l., prevalence of B. miyamotoi in ticks is not negatively affected by the presence of cattle (62,107). Borrelia miyamotoi DNA has been detected in two healthy cats in the USA (108). However, infection of other domestic animals has not been documented so far to the authors' knowledge and no (sero-)prevalence studies have been conducted.…”
Section: Borrelia Miyamotoimentioning
confidence: 90%